Effect of Whey Protein Changes on Milk Flavor and Sensory Characteristics During Heating - Zheting Zhang; Kexin Jiang; Aolin Yang; Kunli Xu; Fanyu Meng; Fang Zhong; Bei Wang (Foods)
The flavor of dairy products crucially affects consumer purchase preference. Although the flavor and sensory perception of milk can be influenced by heat treatment during processing, the exact mechanism remains unclear. Therefore, this study analyzed the whey protein content and structural changes of milk heated at different time and temperature combinations and evaluated the flavor compounds and sensory characteristics of milk. The results showed that higher temperatures changed the secondary milk whey protein structures and gradually increased α-lactalbumin, β-lactoglobulin, and lactoferrin denaturation in the milk. There were differences in sensory characteristics of milk heated at different time and temperature combinations. The correlation analysis indicated that whey protein denaturation was negatively correlated with 1-octen-3-ol (p < 0.05) and positively associated with hexanal, isovaleric acid, γ-nonalactone, methyl palmitate, and phenol (p < 0.01). The changes in the content and secondary structure of whey proteins affected the interaction between flavor compounds and whey protein, which affected the release of flavor compounds. Consequently, the sensory characteristics of milk were influenced. This study provides a theoretical basis for exploring the interaction between whey proteins and flavor compounds.